Analisis Perilaku Perawat Dalam Pengendalian dan Pencegahan Health Care Associated Infections (HAIs) - Mita Mita; Muhammad Ali Maulana; Sukarni Sukarni; Yoga Pramana (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: The treatment room becomes a potential practice for transmitting infections either through direct contact when the patient receives services from a nurse or indirectly through tools, materials, and supporting facilities used in supporting nursing services. Objective: Obtain a description of the nurse's behavior in implementing infection control and prevention in patients. Method: Use a descriptive observational design. The population of this study is nurses in the inpatient section, with a sample number of 60 nurses. Results: Research shows that nurses' behavior in infection prevention and control is still not as good as (60%). Conclusion: Health workers, especially nurses, must apply universal precautions properly to reduce the number of Health Care Associated Infections (HAIs).